Selection of Inductor and Snubber Capactor to Optimize the Size and Efficiency of DC-DC Switching Power Converter - Mahesh Gowda, N. M.; Parthasarathy, S. S. (Asian Journal of Engineering and Applied Technology, 2018)
This paper presents a selection of inductor and snubber capacitor in non-isolated synchronous DC-DC switching power converter. The circuit is made to operate in Synchronous Discontinuous Conduction Mode (SDCM)/Forced Continuous Conduction Mode (FCCM) of operation for minimum inductor value, to reduce the size, weight and cost of the converter. The turn off loss of the switch induced by SDCM of operation is minimized by connecting snubber capacitor across the transistor switch. Before the switch is turned ON, snubber capacitor requires certain amount of energy must be stored in the inductor to discharge the capacitor energy [1]. The question is how much capacitor and inductor value is required. A series of MATLAB script are executed to find minimum inductor value for FCCM of operation and to select snubber capacitor for maximum efficiency. Complementary gate signals are used to control the ON and OFF of main and auxiliary switch. SDCM of operation due to complementary control gate signal scheme, minimum turn on loss of the transistor switch and low diode reverse recovery loss are achieved. Thus the Zero Voltage Resonant Transition (ZVRT) of transistor switch is realized, both turn on and turn off loss is minimized and also removes the parasitic ringing in inductor current.